2008
DOI: 10.1128/aac.00464-08
|View full text |Cite
|
Sign up to set email alerts
|

Fluoroquinolone Enhances the Mutation Frequency for Meropenem-Selected Carbapenem Resistance in Pseudomonas aeruginosa , but Use of the High-Potency Drug Doripenem Inhibits Mutant Formation

Abstract: The mutation frequency for carbapenem resistance in Pseudomonas aeruginosa strains that were selected with carbapenems was enhanced in the presence of subinhibitory concentrations of fluoroquinolones. The mutants showed either a loss of OprD activity or increased mexAB-oprM expression. The highest mutant isolation frequency was obtained by selection with meropenem, while doripenem inhibited mutant growth.The carbapenem group of ␤-lactam antibiotics is highly active against Pseudomonas aeruginosa. In the absenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
50
1
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(54 citation statements)
references
References 29 publications
(36 reference statements)
0
50
1
1
Order By: Relevance
“…everal bactericidal antibiotics have been reported to have low to moderate mutagenic activity when used at subinhibitory or sublethal concentrations (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14), usually ranging from 3-to 8-fold over background levels of spontaneous mutations (with one exception [7]). In particular, ciprofloxacin (CPR) and its close derivative norfloxacin (NOR) display mutagenic activity in different detector systems (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14).…”
mentioning
confidence: 99%
“…everal bactericidal antibiotics have been reported to have low to moderate mutagenic activity when used at subinhibitory or sublethal concentrations (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14), usually ranging from 3-to 8-fold over background levels of spontaneous mutations (with one exception [7]). In particular, ciprofloxacin (CPR) and its close derivative norfloxacin (NOR) display mutagenic activity in different detector systems (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14).…”
mentioning
confidence: 99%
“…In vivo, the proliferative inhibitory effect and maximal bactericidal action correlate with the time for which the drug concentration exceeds its minimum inhibitory concentration MIC ; T MIC . In the present study, we chose DRPM as the antibiotic to be evaluated for the following reasons : 1 DRPM is highly effective against aerobic Gram-negative and Gram-positive bacteria, as well as anaerobic bacteria, and it suppresses the growth of antimicrobial-resistant Pseudomonas aeruginosa ; 2 DRPM, MEPM, and IPM exhibit potent activity, with an MIC 90 of 4, 16, and 32 µg / ml, respectively, and DRPM is clinically effective against P. aeruginosa infection ; 3 DRPM does not show any cross-resistance with MEPM and IPM against P. aeruginosa ; 4 incompatibility between DRPM and protease inhibitors is low ; and 5 DRPM is a drug with little effect on the central nervous system [30][31][32][33][34][35][36] .…”
Section: Discussionmentioning
confidence: 99%
“…50 Response to the effect of fluoroquinolones may differ. Tanimoto et al 54 showed that fluoroquinolones enhanced the carbapenem resistance mutation rate in P. aeruginosa and that the highest mutation isolation frequency occurred during selection with meropenem, whereas doripenem inhibited mutant growth. However, in spite of the differences, the presence of common mechanisms leading to carbapenem resistance to include the emergence of new mechanisms such as the blaKPC-containing Klebsiella pneumo niae (KPC-Kp) isolates confirms that vigilance in monitoring bacterial resistance is warranted.…”
mentioning
confidence: 99%
“…53 In strains of P. aeruginosa passaged over the course of 7 days that had MICs near the expected break point for doripenem (#4 µg/mL), gentamicin maintained or prolonged doripenem potency. 53 Tanimoto et al 54 showed that fluoroquinolones enhance the carbapenem resistance mutation rate in P. aeruginosa and that the highest mutation isolation frequency occurred during selection with meropenem, whereas doripenem inhibited mutant growth.…”
mentioning
confidence: 99%